Regulation of the IgE response by T follicular regulatory cells - Alexander L. Dent (Allergology International)
Allergen-specific IgE is a major mediator of allergic responses and contributes greatly to allergic disease in the human population. Therapies that inhibit the production of IgE would be useful for lessening the burden of allergic disease. A great deal of research has focused on how IgE responses are regulated, and several factors that promote the production of allergic IgE have been characterized. T follicular helper (TFH) cells expressing IL-4 are required for the development of IgE expressing B cells in the germinal center (GC). Ig somatic hypermutation and B cell selection in the GC leads to the development of high affinity allergen-specific IgE that promotes anaphylaxis, a severe form of allergic response. T follicular regulatory (TFR) cells are also found in the GC response and act with TFH cells in the selection of high affinity IgE + B cells. This review examines the current literature on IgE responses and TFR cells. In mouse studies, TFR cells have a suppressive role on IgE responses in allergic airway disease, however TFR cells also play a helper role in the IgE response in food allergy. In human studies, TFR cells correlate with a decreased allergic response but evidence for a direct suppressive role of TFR cells on IgE in vivo is lacking. TFR cells may represent a new target for allergy therapies, but caution must be exercised to promote the suppressor activity of TFR cells and not the helper activity of TFR cells on IgE responses.